The shrine of Eileithyia, Minoan goddess of childbirth and motherhood at the Inatos cave in southern Crete - Hölbl, Günther (Prehistory monographs, 2022)
"This volume is a catalog of the ancient Egyptian imports and Egyptianizing artifacts found in 1962 during the excavation of a cave near Tsoutsouros (ancient Inatos), Crete, Greece. The cave was a sanctuary dedicated to the Minoan and Greek goddess Eileithyia, patron of childbirth and motherhood. The Aegyptiaca of the Minoan-Mycenaean era on Crete were a tangible sign of the political and economic relations between the Aegean rulers and the Egyptian royal court. Certainly some of the Egyptian kings' scarabs that reached Crete from the reign of Amenophis III to the end of the Eighteenth Dynasty are to be explained by official Egyptian-Cretan relations. The statuettes, seals, and vessels are lavishly illustrated with plates of color photographs"--